Nitrogen and climate change : an explosive story - Reay, Dave (Palgrave Macmillan, 2020)
The world is changing. Human population is surging towards 10 billion, food, water, climate and energy security are all at risk. Nitrogen could be our life raft in this global 'perfect storm'. Get it right and it can help to feed billions, fuel our cars and put a dent in global warming. Get it wrong and it will make things a whole lot worse.